#TITLE_ALTERNATIVE# - ROHADI (NIM 22405011), SUPRIYANTO
Many earthquake researchs report that there are any earthquake periodicity in certain magnitude range, in some seismogenics region. Earthquake periodicity related to the earthquake process which is a renewal process, that means energy acumulation renewal in certain period of time after an earthquake occured, before fault ready to release energy in the form of next earthquake. This research based on Gutenberg-Richter’s relation in determining of earthhquake caracteristics. An autoregressive model, continuous wavelet tranform, and stationary wavelet transform used to determine earthquake periodicity patern and to predict seismic activity. We used earthquake catalog of National Earthquake Information Center (NEIC), from 1973 to 2006, in Java Subduction Zone (6,5° S -12,5° S and 105° E -115° E). Earthquake magnitude time series of the catalog with different time step convert to stain energy release which have constant time step. The results of statistical analysis show that there are clearly identified a seismic gap zone in southern of Yogyakarta. Earthquake periodicity based on their depth and sub region did not indicate any certain periodicity. But earhtquake periodicity based on observation period indicates that there are about one year earthquake periodicity and also clearly identified a seismic quiescence before a large earthquakes. Earthquake actvivity trend in west part of the region show that high earhtquake activity in the middle of 2007, seismic activity trend decrease in central region until the end of 2007, but seismic activity consistently increase in eastern part of the region in 2007.